Effect of Biofertilizers and Organic Amendments on Germination and Seedling Growth of Common Dry Zone Forest Species in Sri Lanka: Sustainable Reforestation Practices in Sri Lanka - Neelamanie Yapa; Nadeesha Jayakody; Asanka Madhushan; Anuhansi Pelawatta (Turkish Journal of Agriculture: Food Science and Technology)
Most of the dry zone forests in Sri Lanka are arisen after unsustainable farming practices. Therefore, the natural regeneration of plant species in these forests reported to be very poor due to the reduced soil fertility. This study was conducted to find possible measures for the successful seed germination and seedling establishment of common dry zone forest tree species by sustainable soil fertility management. A pot trial was carried out in a greenhouse at the Faculty of Applied Sciences, Rajarata University, Mihintale, Sri Lanka. The experiment comprised of 128 pots and four replicates. Pots were assigned with different soil fertility managements: T0: control (Top soil only), T1: Arbuscular Mycorrhizal Fungi (AMF), T2: a traditional mixed microbial culture (Jeewamurthum), T3: Compost, T4: Biochar, T5: T1+T2, T6: T1+T3, T7: T1+T4; and different forest plant species: Manilkara hexandra, Feronia limonia, Pterospermum conscens and Bauhinia racemosa. Seed germination percentage was measured two weeks after sowing, and shoot biomass, relative plant growth rate, and AMF colonization percentage were measured after four months of germination. The results revealed that inoculation of AMF enhance the seed germination percentage of all the selected plant species. Both sole and combined application of AMF and compost gives more benefits to all the tested plant species by enhancing all the measured growth parameters. The findings of present study would be useful in reforestation programs of dry zone forests in Sri Lanka by practicing sustainable procedures.